Case of recurrent Flavimonas oryzihabitans bacteremia associated with an implanted central venous catheter (Port-A-Cath): assessment of clonality by arbitrarily primed PCR. - Verhasselt, B (1995)
Flavimonas oryzihabitans bacteremias, which occurred immediately after the flushing or use of an implanted central venous catheter (Port-A-Cath) in two patients at the same pediatric ward, were studied by arbitrarily primed PCR. We conclude that the colonization of the Port-A-Cath with F. oryzihabitans described here lasted for several months.